2022
DOI: 10.1093/plankt/fbac017
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in thermal stress of marine copepods after physiological acclimation

Abstract: We studied the phenotypic response to temperature of the marine copepod Paracartia grani at the organismal and cellular levels. First, the acute (2 days) survival, feeding and reproductive performances at 6–35°C were determined. Survival was very high up to ca. 30°C and then dropped, whereas feeding and fecundity peaked at 23–27°C. An acclimation response developed after longer exposures (7 days), resulting in a decline of the biological rate processes. As a consequence, Q10 coefficients dropped from 2.6 to 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 54 publications
0
15
1
Order By: Relevance
“…In the case of males, there was also a positive trend of feeding rates with temperature in F1 (albeit not significant), which in successive generations also dampened. The drop in thermal response found in males and females in our experiments was greater than that reported for the same species by Saiz et al (2022), who found a decrease in the Q 10 coefficients from 2.6-2.7 for an acute response (24 h) to 1.6-1.7 after a 7-d acclimation. It seems, therefore, that long-term exposure (multigenerational rearing) has deeper effects on the thermal compensation of physiological rates, leveling out the response to temperature and evidencing a notable phenotypic plasticity in the copepod species, which may be related to the coastal environments that constitute its habitat and the broad latitudinal distribution (Saiz et al 2022).…”
Section: Thermal Effects On Physiological Ratescontrasting
confidence: 78%
See 1 more Smart Citation
“…In the case of males, there was also a positive trend of feeding rates with temperature in F1 (albeit not significant), which in successive generations also dampened. The drop in thermal response found in males and females in our experiments was greater than that reported for the same species by Saiz et al (2022), who found a decrease in the Q 10 coefficients from 2.6-2.7 for an acute response (24 h) to 1.6-1.7 after a 7-d acclimation. It seems, therefore, that long-term exposure (multigenerational rearing) has deeper effects on the thermal compensation of physiological rates, leveling out the response to temperature and evidencing a notable phenotypic plasticity in the copepod species, which may be related to the coastal environments that constitute its habitat and the broad latitudinal distribution (Saiz et al 2022).…”
Section: Thermal Effects On Physiological Ratescontrasting
confidence: 78%
“…Based on our results, we explored the relative contribution of body size change and physiological compensation to the dampening of physiological rates that we found in our experiments after multiple generational thermal exposure. To do this, we took the per capita female feeding rates at 19 C for each generation and applied a Q 10 value from literature for P. grani (Q 10 = 1.6; Saiz et al 2022) to estimate the expected temperature-mediated increase in ingestion. Subsequently, we corrected the obtained feeding rates for allometric effects applying a body weight scaling factor of 0.743 (Saiz and Calbet 2007), in order to take into account the decrease in body size (carbon content) at warmer temperatures.…”
Section: Combined Effects Of Thermal Compensation and Body Size Reduc...mentioning
confidence: 99%
“…E) which indicates higher amount of ingested algae and/or higher assimilation e ciency rates. Changes in feeding rates and assimilation e ciency in response to temperature have been reported before for calanoid copepods (Isla et al 2008;Saiz et al 2022) and harpacticoids (Li et al 2015). We hypothesize that total FA content can be maintained at constant levels across temperatures through increasing ingestion rates, assimilation e ciency, or both.…”
Section: Survivalmentioning
confidence: 53%
“…For instance, some authors report evident seasonal fluctuation in acetylcholinesterase (AChE) (e.g., Menezes et al, 2006 ), a key enzyme in cholinergic signal transmission in the sensory and neuromuscular systems that therefore appears to be likely related to animals’ locomotor activity ( Anita et al, 2017 ). Moreover, carboxylesterases (CbE), a multifunctional group of enzymes relevant in lipid synthesis and decomposition and signal transmembrane transduction ( Zang et al, 2020 ), are involved in the metabolism of endogenous compounds ( Nos et al, 2021 ), and thermal stress can compromise their capability to face environmental chemical stressors ( Saiz et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%